2003
DOI: 10.1111/j.1533-8525.2003.tb00525.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Among Adolescent Pregnancy, Pregnancy Resolution, and Juvenile Delinquency

Abstract: We apply criminological theories of social control to cxplorc the rclationships among adolescent pregnancy, pregnancy resolution, and juvenile delinquency. While most ever-pregnant girls have especially high rates of delinquent behavior, adolescent mothers exhibit delinquency levels no higher than those of their never-pregnant peers. Unlike adolescent females who end their pregnancies through abortion, those who keep their babies experience a dramatic reduction in both smoking and marijuana use. Our results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 47 publications
1
31
0
1
Order By: Relevance
“…They experience more stress and time restraints when they have a child and are more likely to stay at home with a child and be the main or only custodian. In line with this reasoning, several studies have found at least a temporally crime reducing effect of parenthood for women (Graham & Bowling, 1995;Hope, Wilder, & A c c e p t e d M a n u s c r i p t 4 Watt, 2003; Kreager, Matsueda, & Erosheva, 2010;Monsbakken et al, 2013) or have found that the majority of young women quit their gang involvement once they became a mother (Fleisher & Krienert, 2004). However, in a US school sample Giordano et al (2011) showed that parenthood alone did not reduce criminal behavior, rather female crime levels reduced only if it was a planned pregnancy.…”
Section: Desistance and Parenthoodmentioning
confidence: 80%
“…They experience more stress and time restraints when they have a child and are more likely to stay at home with a child and be the main or only custodian. In line with this reasoning, several studies have found at least a temporally crime reducing effect of parenthood for women (Graham & Bowling, 1995;Hope, Wilder, & A c c e p t e d M a n u s c r i p t 4 Watt, 2003; Kreager, Matsueda, & Erosheva, 2010;Monsbakken et al, 2013) or have found that the majority of young women quit their gang involvement once they became a mother (Fleisher & Krienert, 2004). However, in a US school sample Giordano et al (2011) showed that parenthood alone did not reduce criminal behavior, rather female crime levels reduced only if it was a planned pregnancy.…”
Section: Desistance and Parenthoodmentioning
confidence: 80%
“…Many scholars have identified childbearing as an impetus for the maturation out of criminal involvement (Enos, 2001;Graham & Bowling, 1996;Hope, Wilder, & Watt, 2003). Children provide high levels of social satisfaction and attachment for women, particularly those living in disadvantaged environments (Edin & Kefalas, 2005;Sharp & Marcus-Mendoza, 2001), and can facilitate the development of a pro-social self image (Giordano et al, 2002).…”
Section: Gendered Pathwaysmentioning
confidence: 99%
“…Put differently, the effect of depression on delinquency is stronger among adolescent mothers relative to those in the reference group (i.e., adult mothers and non-mother adolescents) while holding all other variables in the model constant. This finding is notable because previous research has failed to consider the role of emotions among adolescent mothers when it comes to delinquent involvement (Hope et al, 2003).…”
Section: Multiple Regression Analysesmentioning
confidence: 39%